2018
DOI: 10.1002/jppr.1379
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining practice change in health care: the impact of a national quality improvement program on the uptake of collaborative medicines reviews

Abstract: Aim:We evaluated the impact of quality improvement interventions at different time points on the uptake of collaborative

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Although the duration of use of risperidone decreased in the aged care population following the TGA labelling changes, from a median of 338 days per person prior to the changes to 240 days after, this was still in excess of the new 12-week (84 days) duration recommended by the TGA. Sustaining practice change in healthcare is difficult, and repetition of messages has been shown to improve the duration of healthcare improvements following healthcare interventions [34]. Future health improvement interventions will support a sustained reduction in the rate of use of risperidone for BPSD.…”
Section: Discussionmentioning
confidence: 99%
“…Although the duration of use of risperidone decreased in the aged care population following the TGA labelling changes, from a median of 338 days per person prior to the changes to 240 days after, this was still in excess of the new 12-week (84 days) duration recommended by the TGA. Sustaining practice change in healthcare is difficult, and repetition of messages has been shown to improve the duration of healthcare improvements following healthcare interventions [34]. Future health improvement interventions will support a sustained reduction in the rate of use of risperidone for BPSD.…”
Section: Discussionmentioning
confidence: 99%
“…However, participants in all three studies were predominately community dwelling (6%-20% RACF residents) and were not followed after discharge. Furthermore, evidence suggests that regular interventions reinforcing key messages are most effective for supporting sustained behavior change [38]. Future directions may include evaluation of the reproducibility of intervention effects when the intervention is provided over successive periods as it is possible that repeated simplification may further reduce administration times and other aspects of complexity.…”
Section: Resultsmentioning
confidence: 99%
“…Others have suggested that regular repetition of QI messages are needed to sustain improvements in practice. 35 …”
Section: Discussionmentioning
confidence: 99%